2x(3y-2)+(3y-2)=-55
3y-2(2x+1)=-55
TH1: 3y-2(2x+1)=(-5).11
=> \(\hept{\begin{cases}3y-2=-5\\2x+1=11\end{cases}}\)hoặc \(\hept{\begin{cases}3y-2=11\\2x+1=-5\end{cases}}\)
=> \(\hept{\begin{cases}y=-1\\x=5\end{cases}}\)hoặc \(\hept{\begin{cases}y=\frac{13}{3}\\x=-3\end{cases}}\)(không thỏa mãn do x;y\(\in Z\))
=> \(\hept{\begin{cases}y=-1\\x=5\end{cases}}\)(1)
TH2: 3y-2(2x+1)=5.(-11)
=> \(\hept{\begin{cases}3y-2=5\\2x+1=-11\end{cases}}\)hoặc \(\hept{\begin{cases}3y-2=-11\\2x+1=5\end{cases}}\)
=> \(\hept{\begin{cases}y=\frac{7}{3}\\x=-6\end{cases}}\)(không thỏa mãn do x;y \(\in Z\)) hoặc \(\hept{\begin{cases}y=-3\\x=2\end{cases}}\)
=> \(\hept{\begin{cases}y=-3\\x=2\end{cases}}\)(2)
TH3: 3y-2(2x+1)=(-1).55
=> \(\hept{\begin{cases}3y-2=-1\\2x+1=55\end{cases}}\)hoặc \(\hept{\begin{cases}3y-2=55\\2x+1=-1\end{cases}}\)
=> \(\hept{\begin{cases}y=\frac{1}{3}\\x=27\end{cases}}\)(không thỏa mãn do x;y\(\in Z\)) Hoặc \(\hept{\begin{cases}y=19\\x=-1\end{cases}}\)
=> \(\hept{\begin{cases}y=19\\x=-1\end{cases}}\)(3)
TH4: 3y-2(2x+1)=1.(-55)
=> \(\hept{\begin{cases}3y-2=1\\2x+1=-55\end{cases}}\)hoặc \(\hept{\begin{cases}3y-2=-55\\2x+1=1\end{cases}}\)
=> \(\hept{\begin{cases}y=1\\x=-27\end{cases}}\)hoặc \(\hept{\begin{cases}y=\frac{-53}{3}\\x=0\end{cases}}\)(không thỏa mãn)
=> \(\hept{\begin{cases}y=1\\x=-27\end{cases}}\)(4)
Từ (1),(2),(3) và (4) => \(\hept{\begin{cases}y=-1\\x=5\end{cases}}\);\(\hept{\begin{cases}y=-3\\x=2\end{cases}}\);\(\hept{\begin{cases}y=19\\x=-1\end{cases}}\);\(\hept{\begin{cases}y=1\\x=-27\end{cases}}\)